Self-ignition Properties of Peat, Palm Shell Fibre and Woods - Nugroho, Yulianto Sulistyo (UI Scholars Hub, 2002)
Self-ignition properties of peat, palm shell fibre and woods. Forest fire is one of the greatest environmental problems faced by Indonesia. Forest fires have destroyed million hectares of forest and land which cause economic loss, social problems including smoke related diseases and environmental disaster with long time consequences. The exothermic reactions of forest fuels that lead to fire can be initiated by a piloted flame and low-temperature oxidation mechanism. This paper presents the results of low temperature oxidation studies using forests fuel samples i.e. palm shell fibre, peat, woods and low-rank coal. The measured values of the critical oven temperatures and the kinetic oxidation parameters are used to analyze the intrinsic properties of the samples to self-ignite. Thermal runaway reactions leading to ignition are indicated for all forest fuels tested. This reaction is affected by various factors including oven temperature, moisture content, chemical and physical properties as well as basket sizes. Attempt to extrapolate the results of these laboratoryscaled experiments for real fires still require further tests and assessments.